ANALISIS SEASONED EQUITY OFFERINGS TERHADAP KINERJA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA - Andri Novius (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2011)
The purpose of this study is to compare financial performance and stock performance of Seasoned Equity Offerings through financial ratios and stock return. Population of this research are the 28 entities that listed in that listed in Indonesia Stock Exchange. With purposive sampling method, at last 10 entities selected.The dimensions of financial performance include liquidity ratio, leverage profitabilitas turnover and market ratio, hereas stock performance includes stock return.Statistics were tested to find the defference performance variable before and after SEO by using SPSS ver. 16 The result shows that Net Profit Margin experience the descent that indicates the defferences after offerings. Paired Sampel t-test shows that there is no defference for the period before and after SEO. Anova tested shows that there is the difference in financial ratios and stock ratios before and after SEO.